2023
DOI: 10.1007/s40261-023-01257-8
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Continuous Infusion of Cefiderocol in Conjunction with the Establishment of Therapeutic Drug Monitoring in Patients with Extensively Drug-Resistant Gram-Negative Bacteria

Abstract: Background and Objective Resistance to antibacterial substances is a huge and still emerging issue, especially with regard to Gram-negative bacteria and in critically ill patients. We report a study in six patients infected with extensively drug-resistant Gram-negative bacteria in a limited outbreak who were successfully managed with a quasi-continuous infusion of cefiderocol. Methods Patients were initially treated with prolonged infusions of cefiderocol over 3 h every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“… 11 So far, only a few studies reported the results of cefiderocol therapeutic drug monitoring. 12 , 13 Prinz et al measured a median (interquartile range) trough concentration of 50.0 (27.2–74.6) mg/L in five critically ill patients. Gatti et al reported trough plasma concentrations of the free fraction ranging from 0.59 to 56.78 mg/L in 13 patients.…”
Section: Resultsmentioning
confidence: 99%
“… 11 So far, only a few studies reported the results of cefiderocol therapeutic drug monitoring. 12 , 13 Prinz et al measured a median (interquartile range) trough concentration of 50.0 (27.2–74.6) mg/L in five critically ill patients. Gatti et al reported trough plasma concentrations of the free fraction ranging from 0.59 to 56.78 mg/L in 13 patients.…”
Section: Resultsmentioning
confidence: 99%
“…In critically ill patients treated with continuous infusion of β‐lactams, an unbound concentration of >5 times the MIC is suggested 16 . However, limited information on cefiderocol as continuous infusion (CI) and its true therapeutic target has been assessed 17,18 …”
Section: Introductionmentioning
confidence: 99%